Chi-Ju-Di-Huang-Wan protects rats against retinal ischemia by downregulating matrix metalloproteinase-9 and inhibiting p38 mitogen-activated protein kinase. Issue 1 (December 2016) - Cheng, Ji-Min; Liu, Xiao-Qian; Liu, Jorn-Hon; Pan, Wynn; Zhang, Xiu-Mei; Hu, Lei; Chao, Hsiao-Ming
Abstract Background Retinal ischemia is a retinal disorder related to retinal vascular occlusion, glaucoma, diabetic retinopathy and age-related macular degeneration. The study aimed to evaluate the protective effects and underlying mechanisms of Chi-Ju-Di-Huang-Wan (CJDHW) against retinal ischemia in rats. Methods High intraocular pressure (HIOP)-induced retinal ischemia was established in Wistar rats by raising their intraocular pressure to 120 mmHg for 60 min with in an eye whose anterior chamber was cannulated with a 30-guage needle adapted to a normal saline bottle through an intravenous line. This ischemic insult was followed by 1 or 7 days of reperfusion. The effects of CJDHW were studied by (i) electroretinogram (ERG); (ii) real-time polymerase chain reaction to determine the retinal mRNA levels of Thy-1 and matrix metalloproteinase-9 (MMP-9); (iii) Western blot analysis to determine the retinal protein levels of B cell lymphoma 2 (Bcl-2), heme oxygenase-1 (HO-1), phosphorylated-p38 mitogen-activated protein kinase (P-p38 MAPK) and MMP-9; (iv) hematoxylin and eosin (HE) staining; (v) fluorogold retrograde labeling; and (vi) terminal deoxynucleotidyl-transferase (TdT)-mediated dUTP nick end-labeling (TUNEL) apoptosis assay. Moreover, after fixation with 4 % paraformaldehyde and 30 % sucrose, the isolated retinas were sectioned and immunolabeled with goat anti-choline acetyltransferase (ChAT) polyclonal antibody, mouse anti-vimentin monoclonal antibody and rabbit anti-glial fibrillary acidic protein (GFAP) polyclonal antibody. The retinal sections were then incubated with rhodamine-conjugated rabbit anti-goat antibody, fluorescein isothiocyanate (FITC)-conjugated goat anti-mouse IgG or FITC-conjugated goat anti-rabbit IgG. A daily oral intake of 3 mL of water (vehicle; Group 2) or CJDHW (2.8 or 4.2 g/kg/day; CJDHW2.8 or CJDHW4.2; Group 3 or 4) was given for 7 consecutive days either before (preischemic drug administration) or after HIOP-induced retinal ischemic injury (postischemic drug administration). In Group 5, an intravitreal injection of 4 μL of 0.5 mM SB203580 (p38 MAPK inhibitor) was performed on the ischemic eye 15 min before retinal ischemia. The control rats received a sham procedure (Group 1) where the saline reservoir was not raised. Results The ischemia-induced changes (Group 2) were significantly modulated by pretreating the rats with 4.2 g/kg/day of CJDHW (Group 4; ERG:P  < 0.001 on I/R day 7; HE stain:P  < 0.001 on I/R day 7; TUNEL:P  = 0.05 on I/R day 7; retrograde labeling:P  = 0.007 on I/R day 7; Thy-1 mRNA:P  = 0.02; MMP-9 mRNA:P  < 0.001; Bcl-2 protein:P  = 0.02; HO-1 protein:P  = 0.03; P-p38 MAPK protein:P  < 0.001; MMP-9 protein:P  = 0.02). These modulations included the following features (Group 2 vs. 4), increased ERG b-wave amplitudes (0.38 ± 0.04 vs. 0.81 ± 0.03), increased inner retinal thickness (45.08 ± 2.85 vs. 67.98 ± 5.48 μm), increased ChAT immunolabeling, decreased vimentin/GFAP immunoreactivity, less numerous apoptotic cells in the ganglion cell layer (1.40 ± 0.55 vs. 0.60 ± 0.55), and more numerous retinal ganglion cells (887.73 ± 158.18 vs. 1389.02 ± 53.20). Moreover, increased Thy-1 (0.31 ± 0.15 vs. 0.78 ± 0.32) and decreased MMP-9 mRNA levels were found (4.44 ± 0.84 vs. 1.13 ± 0.34), respectively. Furthermore, the Bcl-2 protein level (0.78 ± 0.08 vs. 1.80 ± 0.34) was increased while the HO-1 (0.99 ± 0.20 vs. 4.15 ± 2.08), P-p38 MAPK (1.12 ± 0.18 vs. 0.57 ± 0.18) and MMP-9 levels were decreased (0.70 ± 0.23 vs. 0.39 ± 0.10). The ischemia-associated increases in P-p38 and MMP-9 protein levels were also attenuated by 0.5 mM SB203580 (P-p38 MAPK: 1.12 ± 0.18 vs. 0.18 ± 0.07, P  < 0.001; MMP-9: 0.70 ± 0.23 vs. 0.21 ± 0.07, P  = 0.002). This was also the case to the MMP_enzyme activity (Group 2 vs. 4: 5.03 ± 1.57 vs. 1.59 ± 0.47, P  = 0.002; Group 2 vs. 5: 5.03 ± 1.57 vs. 1.35 ± 0.41, P  = 0.001). Conclusion Treatment of the rats suffering from retinal ischemia with CJDHW inhibited apoptosis, increased antioxidative activity, downregulated MMP-9 and inhibited p38 MAPK.